THE INFLUENCE OF HEALTH EDUCATION ON STRENGTHENING AND UNDERSTANDING COVID-19 ON STUDENT ANXIETY LEVEL - Wahidyanti Rahayu Hastutiningtyas; Yanti Rosdiana; Srijatun Srijatun (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Coronavirus disease (COVID-19) is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV2) virus. In 2021 the government changes the learning system again to a face-to-face system so that students need to adapt again to carry out the face-to-face learning process wherein this condition students must be able to understand covid-19. Objectives: This study was to determine the Effect of Health Education on Strengthening and Understanding Covid-19 on Anxiety Levels of Students at SMP Negeri 26 Malang City. Methods: This study uses an analytical observation design with a Quasy Experiment approach. The population is 100 students and the sample is taken according to the inclusion and exclusion criteria, determined by a simple random sampling technique as many as 80 students. Collecting data using a questionnaire sheet instrument on anxiety levels using HARS (Hamilton Rating Scale for Anxiety) and providing health education treatment about Strengthening and Understanding Covid-19. Anxiety Level Results Students in the group before being given Health Education on Strengthening and Understanding Covid-19 had an average posttest score of 50.3, while after being given the treatment, they had a pretest average score of 70.48. The group experienced a decrease of 20.18. The analysis used is if the data is normally distributed, then Paired t-test parametric data analysis is used and if the data is not normally distributed then non-parametric data analysis is used in the form of Wilcoxon Matched-Pairs Signed-Ranks Test. The results of the analysis carried out that the data obtained were not normally distributed so that the Wilcoxon data test was carried out. The basis for decision-making is based on the 95% confidence level or = 0.05. If p < 0.05 then H0 is rejected and H1 is accepted. Results: Based on the results of this study, there is an effect of Health Education on Strengthening and Understanding of Covid-19 on Students' Anxiety Levels at SMP Negeri 26 Malang City with an Asymp score. Sig. (2-tailed) = 0.000. Conclusion: The results of this study, students at SMP Negeri 26 Malang City have knowledge and understanding about Covid-19 and the anxiety experienced by students have decreased.